2022
DOI: 10.1002/hbm.26081
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multiband and multiband multiecho gradient‐echo EPI for task fMRI at 3 T

Abstract: A multiband (MB) echo‐planar imaging (EPI) sequence is compared to a multiband multiecho (MBME) EPI protocol to investigate differences in sensitivity for task functional magnetic resonance imaging (fMRI) at 3 T. Multiecho sampling improves sensitivity in areas where single‐echo‐EPI suffers from dropouts. However, It requires in‐plane acceleration to reduce the echo train length, limiting the slice acceleration factor and the temporal and spatial resolution Data were acquired for both protocols in two sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…The literature suggests a MB acceleration factor of four improves cortical FC reliability, while a single band sequence is preferred for subcortical regions (M. Cahart et al, 2023;M.-S. Cahart et al, 2022). Further, the combination of multiband and multiecho sequences promise to yield higher reliability estimates than MB sequences alone (Cohen et al, 2021;Fazal et al, 2023;Lynch et al, 2020) (Finn, 2021;Meer et al, 2020;Sonkusare et al, 2019), thus leading to increases in reliability. Such improvements in reliability were found across all brain regions in a study that compared test-retest reliability of FC measures between movie-watching and rest (Wang, Ren, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests a MB acceleration factor of four improves cortical FC reliability, while a single band sequence is preferred for subcortical regions (M. Cahart et al, 2023;M.-S. Cahart et al, 2022). Further, the combination of multiband and multiecho sequences promise to yield higher reliability estimates than MB sequences alone (Cohen et al, 2021;Fazal et al, 2023;Lynch et al, 2020) (Finn, 2021;Meer et al, 2020;Sonkusare et al, 2019), thus leading to increases in reliability. Such improvements in reliability were found across all brain regions in a study that compared test-retest reliability of FC measures between movie-watching and rest (Wang, Ren, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cahart et al, 2022). Further, the combination of multiband and multiecho sequences promise to yield higher reliability estimates than MB sequences alone (Cohen et al, 2021; Fazal et al, 2023; Lynch et al, 2020). Congruent to increasing scan lengths and emerging neuroimaging protocols, our findings postulate that task conditions also increase FC‐TRC in specific regions and the choice of task used in a study may directly impact FC reliability of those regions.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow up study, Kirilina et al, (2016) showed greater task activation during emotional and reward-based learning in orbitofrontal cortices, most likely due to effective recovery of signal in these susceptible areas, but less activation in deep brain regions, most likely due to higher acceleration and/or smaller voxel size. Similarly, Fazal et al, (2023) showed that multi-echo multi-band had greater sensitivity in areas affected by signal inhomogeneity but multi-band only did show greater sensitivity in visual areas (not deep brain regions).…”
Section: Introductionmentioning
confidence: 91%
“…This is most likely due to lower tSNR in brain regions that are further from the receiver coils, which is exaggerated when using higher gfactors for in-plane acceleration (Kirilina et al, 2016). Although, Fazal et al, (2023) showed that multi-echo multi-band had reduced sensitivity in visual and anterior cingulate regions compared to multi-band only during a Stroop task.…”
Section: Advantages and Disadvantages Of Multi-echo Protocolsmentioning
confidence: 99%
See 1 more Smart Citation